2014
DOI: 10.1128/genomea.01217-14
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomes from Thawing Low-Soil-Organic-Carbon Mineral Cryosols and Permafrost of the Canadian High Arctic

Abstract: Microbial release of greenhouse gases from thawing permafrost is a global concern. Seventy-six metagenomes were generated from low-soil-organic-carbon mineral cryosols from Axel Heiberg Island, Nunavut, Canada, during a controlled thawing experiment. Permafrost thawing resulted in an increase in anaerobic fermenters and sulfate-reducing bacteria but not methanogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Sequence abundance information from metagenomic data gathered from the 5‐cm cryosol samples from the same site (Chauhan et al ., ; Stackhouse et al ., ) was used to estimate that the total methanotrophic population should account for up to ~1% of the cellular community with a higher proportion of type II methanotrophs at the surface (~0.8% of total sequences) than in the permafrost (~0.1% of total sequences). Total counts of bacterial, archaeal, and eukaryotic cells determined by FISH averaged 9.8 ± 5.2 × 10 8 cells g −1 , with bacteria accounting for 82 ± 11% of cell counts and no statistical difference between depths ( P = 0.46, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence abundance information from metagenomic data gathered from the 5‐cm cryosol samples from the same site (Chauhan et al ., ; Stackhouse et al ., ) was used to estimate that the total methanotrophic population should account for up to ~1% of the cellular community with a higher proportion of type II methanotrophs at the surface (~0.8% of total sequences) than in the permafrost (~0.1% of total sequences). Total counts of bacterial, archaeal, and eukaryotic cells determined by FISH averaged 9.8 ± 5.2 × 10 8 cells g −1 , with bacteria accounting for 82 ± 11% of cell counts and no statistical difference between depths ( P = 0.46, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A sulfur-reducing bacterium was isolated from ancient permafrost (Vatsurina et al 2008), and 16S rRNA gene sequences from sulfate-reducing and sulfur-oxidizing bacteria were found in permafrost (Hansen et al 2007, Steven et al 2007). Taxonomic assignment of metagenomic sequences to sulfate reducers and the presence of genes involved in sulfate reduction also revealed that microbes that use sulfate as a TEA are present in permafrost (Chauhan et al 2014, Lipson et al 2013.…”
Section: Sulfur Cyclementioning
confidence: 98%
“…Archaea have also been observed in Arctic and Antarctic soils, albeit at very low abundance [39][40][41]. Low abundance levels are not necessarily indicative of the functional importance of these taxa, as the archaeal taxa identified are typically associated with unique functional properties, such as methanogenesis [42 ].…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 99%
“…However, very few studies have assessed the diversity of viruses in cold environments, let alone their functional roles. Of these published studies on polar habitats, mostly focus on lacustrine systems [54,55] with only very limited surveys of polar edaphic metaviromes [40,56]. The latter suggests that viruses in cold soil environments are highly diverse but are typically dominated by Mycobacterium phages [56].…”
Section: Microbial Diversity In Cold Environmentsmentioning
confidence: 99%